Measuring Trust: Experiments and Surveys in Contrast and Combination - Michael Naef; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Trust is a concept that has attracted - significant attention in economic theory and research within the last two decades: it has been applied in a number of contexts and has been investigated both as an explanatory and as a dependent variable. In this paper, we explore the questions of what exactly is measured by the diverse survey-derived scales and experiments claiming to measure trust, and how these different measures are related. Using nationally representative data, we test a commonly used experimental measure of trust for robustness to a number of interferences, finding it to be mostly unsusceptible to stake size, the extent of strategy space, the use of the strategy method, and the characteristics of the experimenters. Inspired by criticism of the widespread trust question used in many surveys, we created a new, improved survey trust scale consisting of three short statements. We show that the dimension of this scale is distinct from trust in institutions and trust in known others. Our new scale is a valid and reliable measure of trust in strangers. The scale is valid in the sense that it correlates with trusting behaviour in the experiment. Furthermore, we demonstrate that the test-retest reliability of six weeks is high. The experimental measure of trust is, on the other hand, not significantly correlated with trust in institutions nor with trust in known others. We therefore conclude that the experimental measure of trust refers not to trust in a general sense, but specifically to trust in strangers.
Keywords: C83; C91; D63; Z13; 330; Trust; experiment; survey; representativity; SOEP